2022
DOI: 10.1101/2022.09.08.507175
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Robust control of replication initiation in the absence of DnaA-ATP ↔ DnaA-ADP regulatory elements inEscherichia coli

Abstract: Replication initiation, especially the widely conserved master initiator protein DnaA, is one of the most well-studied biological problems in bacteria. Specifically, conversion between the ATP and ADP form of DnaA during growth is critical for initiation control. In Escherichia coli, the regulatory elements for conversion have been discovered and extensively characterized over decades. However, they are not widely conserved in bacteria, raising questions on how to generalize the findings in E. coli to other or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(36 citation statements)
references
References 85 publications
7
20
0
Order By: Relevance
“…The effective Hill coefficient lies therefore in the range n eff = 29−38 (vertical dotted grey lines), corresponding to a coefficient of variation of CV=0.05-0.07. This agrees well with the experimentally measured precision of the initiation volume of CV≤0.1 [22,23,135]. Interestingly, the average degree of synchrony at n eff = 30 and n eff = 40, respectively, is given by 〈s〉(n eff = 30) = 0.975 and 〈s〉(n eff = 40) = 0.996, corresponding to the probabilities to fire all origins synchronously of 〈P (∆t < τ l )〉(n eff = 30) ≡ P s (n eff = 30) = 95.5% and P s (n eff = 40) = 98.9%.…”
Section: Synchronous Replication Initiation Of Multiple Originssupporting
confidence: 91%
See 2 more Smart Citations
“…The effective Hill coefficient lies therefore in the range n eff = 29−38 (vertical dotted grey lines), corresponding to a coefficient of variation of CV=0.05-0.07. This agrees well with the experimentally measured precision of the initiation volume of CV≤0.1 [22,23,135]. Interestingly, the average degree of synchrony at n eff = 30 and n eff = 40, respectively, is given by 〈s〉(n eff = 30) = 0.975 and 〈s〉(n eff = 40) = 0.996, corresponding to the probabilities to fire all origins synchronously of 〈P (∆t < τ l )〉(n eff = 30) ≡ P s (n eff = 30) = 95.5% and P s (n eff = 40) = 98.9%.…”
Section: Synchronous Replication Initiation Of Multiple Originssupporting
confidence: 91%
“…Later, Skarstad et al confirmed the prediction of Cooper and Helmstetter by counting the numbers of origins in rapidly growing cultures: They found that most cells have 2 n (n = 1, 2, 3) copies of their chromosome and only a small fraction of cells (2-7%) contained 3, 5, 6 or 7 chromosomes [134]. Recent single cell measurements indeed show that E. coli initiates replication synchronously at up to eight origins with a very high precision in the fast growth regime [22,135]. It remains however an open question how E. coli achieves such a high degree of synchrony.…”
Section: Our Analysis Thus Reveals That the Low CV Of The Initiation ...supporting
confidence: 71%
See 1 more Smart Citation
“…In summary, here we show that in single cells, for all the promoters studied here, the volume- ers [36] shows that the DNA replication cycle is very similar to the wild type strain when RIDA and the other DnaA activity regulators, datA and the DARS sites, are inactive, showing that the inherent ATP hydrolysis activity of DnaA can be sufficient to drive a stable replication cycle. Further work will be required to determine how the activity of these different regulatory factors maintains a robust replication program in the presence of perturbations such as growth shifts or DNA damage [75,76].…”
Section: Discussionmentioning
confidence: 54%
“…On the other hand, the increase in DnaA-ATP required for the initiation of a new DNA replication cycle depends in part on the timely accumulation of newly expressed protein [6,25,32] and the binding of DnaA to the DARS1 and DARS2 sites contributes to a further change in the DnaA-ATP to DnaA-ADP ratio by favoring the exchange of the DnaA-bound nucleotide [6,[33][34][35]. A recent study has shown that in the absence of RIDA, datA and DARS-dependent regulation, the intrinsic ATP hydrolysis activity of DnaA suffices to maintain a near-wild type replication cycle [36].…”
mentioning
confidence: 99%